Update on pleural diseases - 2007 - Bishay, Ayman (Medknow Publications, 2007)
BACKGROUND: New information is available on pleural diseases. The authors selected articles to make recommendations on diagnostic and treatment aspects of pleural diseases. MATERIALS AND METHODS: Eleven articles published in the English language between 2004 and 2007 were chosen. The basis of selection of the articles was the impact on daily practice, change in prior thinking of a disease process or specific treatment modality, as well as proper design and execution of the study. 5-amino-laevulinic acid with fluorescent light combined with white light may allow further diagnostic yield in undiagnosed pleural disease. FDG-PET may allow prognostication of patients with pleural tumors. Utilizing ultrasound by trained Emergency Department physicians is a rapid and effective technique to evaluate non-traumatic pleural effusions in symptomatic patients. Serum osteopontin levels may distinguish patients exposed to asbestos with benign disease from those with pleural mesothelioma. Administration of streptokinase in patients with empyema does not need for surgical drainage, length of hospital stay, or mortality as compared to conventional treatment with chest tube drainage and intravenous antibiotics. Silver nitrate may be an alternative agent to talc for producing pleurodesis. Routine use of graded talc (50% particles greater than 25 microns) is recommended to reduce the morbidity associated with talc pleurodesis. Study design does not permit us to conclude that aspiration of spontaneous pneumothorax is as effective as chest tube drainage. Pleural catheter may prove to be an important palliative modality in treating debilitated patients or patients with trapped lung who show symptomatic improvement with drainage; however, at the present time, these catheters cannot be considered a first line treatment option for patients with malignant pleural effusion. One of the studies reviewed showed no significant difference in tract metastasis in patients with malignant mesothelioma undergoing an invasive pleural procedure with or without irradiation to the procedure site. However, the design of the trial does not allow us to make this conclusion at the present time.